Analisis Kinerja Keuangan Sebelum dan Sesudah Penerapan E-Commerce pada Perusahaan Ritel yang Terdaftar di BEI: indonesia - Geo Ginantaka, Prafangasta Geo Ginantaka; Franciskus Antonius Alijoyo (Universitas Pasundan, 2025)
The development of information technology, especially the emergence of e-commerce, has fundamentally transformed the business paradigm worldwide, including in Indonesia. For retail companies listed on the Indonesia Stock Exchange (IDX), the implementation of e-commerce is a strategic necessity to compete in an increasingly digital market. The Industry 4.0 revolution brings rapid and disruptive changes that will impact almost every industry. The introduction of e-commerce is an effort to mitigate the risk of bankruptcy for companies in the Industry 4.0 era. Before the emergence of e-commerce, retail relied on traditional business models, but with the advent of e-commerce, consumers can shop without geographical or time constraints. The use of e-commerce is increasing in Indonesia, and the value of transactions continues to rise. This phenomenon also affects the retail industry, especially during the COVID-19 pandemic, where offline sales declined, and many retail stores closed. The aim of this research is to analyze the financial performance of retail companies before and after the introduction of e-commerce on the IDX. A descriptive quantitative method is employed using secondary data from annual reports of retail companies. The analysis includes profitability, liquidity, operational efficiency, and business growth. The findings of this research provide insights to stakeholders, investors, management, and regulators, assisting retailers in optimizing e-commerce to enhance financial performance and competitiveness in an increasingly competitive market. This is expected to provide strategic guidance